Výroba součásti "DRŽÁK" - Wagner, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Diplomová práce vypracovaná v rámci magisterského studia oboru 2303T010 předkládá návrh technologie výroby držáku. Na základě literární studie problematiky hlubokého tažení a výpočtů bylo navrženo tažení v nástroji, dle výkresové dokumentace 2-5M68-12/00. K vysunutí součásti je použit vyhazovač. Tažidlo využívá obvyklých komponent upnutých na výstředníkovém naklápěcím lisu LESP 63 A (výrobce ŠMERAL Brno, závod Trnava), s nominální tažnou silou 1000 kN. Tažník a tažnice jsou vyrobeny ze slitinové nástrojové oceli 19 573, tepelně zpracované podle výkresové dokumentace.

The diploma thesis is elaborated within frame of masters study programme 2303T010. The work is submitting design of technology production of the drawn part – the holder. The work is based on the study of problems of the deep drawing process and related calculation was designed drawing in instrument with holder according to drawing documentation 2-5M68-12/00. The lower ejector is using for extrusion component. The drawing instrument make use of standardised components and it is solving forms of customary stool close-set on the crank drawing inclinable press LESP 63 A (producer ŠMERAL Brno, plant Trnava), with nominal tensile force 1000 kN. Drawing punch and drawing die are produced from alloyed instrumental steel 19 573, heat-worked according to drawing documentation.
Production single parts "HOLDER"
Keywords: Tváření; mezní přetvoření; tažení.; Forming; marginal transformation; deep drawing